2014
DOI: 10.1186/2008-2231-22-28
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cichorium intybus extract on the maturation and activity of dendritic cells

Abstract: BackgroundCichorium intybus is a medicinal plant commonly used in traditional medicine for its benefits in immune-madiated disorders. There are several evidences showing that C. intybus can modulate immune responses. In the present study we have investigated the effects of the ethanolic root extract of this plant on the immune system by targeting dendritic cells (DCs). For this purpose, phenotypic and functional maturity of murine DCs after treatment with the extract was analyzed by flow cytometry and mixed ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…There are several evidences showing that C. intybus can modulate immune responses. Karimi et al [ 57 ] studied the effect of ethanolic extract of chicory root on the immune system by targeting mouse dendritic cells. C. intybus at higher concentrations inhibited proliferation of allogenic T cells and in lower concentrations changed the level of cytokines such that IL-4 decreased and IFN-γ increased.…”
Section: Health-promoting Propertiesmentioning
confidence: 99%
“…There are several evidences showing that C. intybus can modulate immune responses. Karimi et al [ 57 ] studied the effect of ethanolic extract of chicory root on the immune system by targeting mouse dendritic cells. C. intybus at higher concentrations inhibited proliferation of allogenic T cells and in lower concentrations changed the level of cytokines such that IL-4 decreased and IFN-γ increased.…”
Section: Health-promoting Propertiesmentioning
confidence: 99%
“…The hydroethanolic extraction of turmeric was also found to reduce the activation of human DCs in response to inflammatory cytokines, and to inhibit DC ability to stimulate the mixed lymphocyte reaction [ 37 ]. Similarly, ethanolic root extract of Cichorium intybus , a traditional medicine, was found to inhibit T-cell proliferation, while low concentrations can modulate cytokine secretion toward a Th1 pattern as shown by increased production of IFN-γ [ 38 ].…”
Section: Modulation Of DC Activitiesmentioning
confidence: 99%
“…intybus, another plant that has been used traditionally to control gallstones, appetite loss, gout, jaundice, skin swellings, rheumatism and liver inflammation, was studied by Karimi et al They showed that higher concentrations of C. intybus extract will inhibit T-cell stimulating activity of DCs, while its lower concentrations can modulate cytokine secretion toward a Th1 pattern [93].…”
Section: Curcuminmentioning
confidence: 99%